Distance measurement using proximity sensor in pedestrian and bicycle navigation - shebl, Mohamed; El-Tokhey, Mohamed; Fathy, Tamer; Mogahed, Yasser; El-Habiby, Mohamed (International Journal of Engineering and Technology, 2018)
Navigation plays an important role in life where it has applications in many disciplines such as transportation services and infrastructure maintenance. Navigation applications depend on reliable, trustful and continuous navigation solution that overcomes the Global Navigation Satellite System (GNSS) denied environments. To achieve this issue, GNSS is now commonly used with other navigation systems such as Inertial Navigation System (INS). Pedestrian dead reckoning usually uses the resultant of 3-axes accelerometer values for step detection; the randomness of the pedestrian hand-held habit the step detection cannot always be accurate by using the accelerometer sensor data. Furthermore, the signal trend of the accelerometer could differ significantly due to the carrying modes and the userâ€™s hand high dynamics.This paper represents a new idea for distance measurement during dead reckoning navigation depending on the proximity sensor which attached to most smartphones to lock screen while making calls for power saving. The new idea summarized in using the proximity sensor for steps counting in case of pedestrian dead reckoning (PDR) or cycles counting in case of bicycle dead reckoning (CDR).In PDR the distance measurement is depending on counting number of steps and knowing the stride length of user which is variable from person to other, so a least square models have been constructed to estimate the stride length of person depending on his height, weight ,age and gender.Although stride length estimation for users but the PDR has a less accuracy comparing with CDR where the stride length can be changed while walking and cannot be controlled like cycle length.The experiments proved that the proximity sensor is a good tool in detecting number of steps and cycles in PDR and CDR respectively, the bicycle mode gives more accurate results in distance measurements compared with walking mode where the average error in case of PDR= 2 % and in case of CDR=0.53 % .Â Â